Tinjauan Hubungan Antara Kebiasaan Sarapan, Kebiasaan Jajan Dan Asupan Zat Gizi Dengan Kekurangan Energi Kronis Pada Siswi SMAN 18 Makassar - Novi Sari; Husnul Khatimah (Direktorat Politeknik Kesehatan Makassar, 2024)
n adolescence there are often health problems related to nutrient intake, tend to experience malnutrition (calories and protein), the habit of skipping breakfast and unhealthy snacking habits that can lead to chronic energy deficiency (CED). This study aims to determine the relationship between breakfast habits, snack habits and nutritional intake with the incidence of chronic energy deficiency in female students at SMAN 18 Makassar. The research design used was cross sectional. The population in this study was all 504 young women in class XI and XII at SMA Negeri 18 Makassar. A total of 54 female students were selected as samples using simple random sampling. Data collected included breakfast habits and snack habits by direct interviews using questionnaires, nutrient intake was obtained using the 24-hour food recall method, and nutritional status was determined based on mid-upper arm circumference (MUAC) measurements. The results showed that there were 59.2% of students who had frequent breakfast habits and 79.6% of students who had frequent snacking habits. There were 88.9% of students with a category of insufficient energy intake and 77.8% of students with a category of insufficient protein intake. It was also found that 59.3% students experienced CED. There is no relationship between breakfast habits, snacking habits, energy and protein intake with Chronic Energy Deficiency in students at SMAN 18 Makassar (p value>0.05). However, the proportion of students with low energy and protein intake was more likely to experience chronic energy deficiency. The conclusion in this study is that there is no relationship between breakfast habits, snacking habits, and nutrient intake with the incidence of chronic energy deficiency.